Red again - Lehman, Barbara (Boston ; New York : Houghton Mifflin Harcourt, 2017)
When a young boy finds an abandoned book, he discovers another world just as real as his own.
Keywords: Books -- Juvenile fiction; Books and reading -- Juvenile fiction; Friendship -- Juvenile fiction; Stories without words; Books -- Fiction; Friendship -- Fiction; Stories without words; Picture books